Guanidine fuels rapid resurrection of desert cyanobacteria - Jin-Long Shang; Guo-Wei Qiu; Lei Zhao; Hai-Feng Xu; Yao Cheng; Yong Li; Zhong-Chun Zhang; Guo-Zheng Dai; Shengwei Hou; Chen Yang; Wolfgang R. Hess; Bao-Sheng Qiu (Proceedings of the National Academy of Sciences, 2026)
In desert ecosystems, microbial activity is driven by brief hydration pulses but is severely limited by persistent nutrient scarcity. Cyanobacteria serve as essential pioneer photoautotrophs, maintaining biogeochemical cycles and ecosystem stability in these arid landscapes. However, their ability to quickly reactivate after rehydration is critically restricted by nitrogen availability. Although the nitrogen demand can be met later by biological nitrogen fixation, it is ineffective and irrelevant during early rehydration due to the high energy costs and delayed activation of nitrogenase, creating a critical metabolic bottleneck. Here we demonstrate that the desert cyanobacterium Nostoc flagelliforme overcomes this limitation by activating a previously overlooked guanidine carboxylase pathway, which sustains the rapid remobilization of internal nitrogen reserves upon rehydration. Transcriptional analysis using a luciferase reporter system reveals that pathway activity is tightly coupled to both hydration and nitrogen status. Disruption of the guanidine-specific riboswitch abolishes induction of the guanidine carboxylase pathway, underscoring its essential role in recovery from desiccation. Furthermore, comparative genomics reveals that the genes encoding this pathway, along with its cognate riboswitch, are widespread among terrestrial cyanobacteria. Phylogenetic analysis indicates they were acquired via horizontal gene transfer from nonphotosynthetic bacteria. Our findings establish an ecological role for guanidine in desert ecosystems and uncover a conserved mechanism that aids cyanobacterial resilience in xeric environments.